2018
DOI: 10.1111/1462-2920.14477
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of the mesophilic Thermotogae genus Mesotoga reveals phylogeographic structure and genomic determinants of its distinct metabolism

Abstract: Summary The genus Mesotoga, the only described mesophilic Thermotogae lineage, is common in mesothermic anaerobic hydrocarbon‐rich environments. Besides mesophily, Mesotoga displays lineage‐specific phenotypes, such as no or little H2 production and dependence on sulfur‐compound reduction, which may influence its ecological role. We used comparative genomics of 18 Mesotoga strains (pairwise 16S rRNA identity >99%) and a transcriptome of M. prima to investigate how life at moderate temperatures affects phylogeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 65 publications
(122 reference statements)
0
20
0
Order By: Relevance
“…Nitrosococcus genus are Ammonia Oxidizing Bacteria (AOB), adapted to saline and acidic environments, regularly found in marine environments but less commonly detected in waste water treatment reactors (Fumasoli et al 2017). Mesotoga are frequently found in oil-polluted marine mesophilic anaerobic environments (Nesbø et al 2019). Brooklawnia species are nonmotile, mesophilic, neutrophilic facultative anaerobic bacteria that have been previously identified in chlorosolvent-contaminated environments (da Costa et al 2015) and Syntrophorhabdus are as well nonmotile, mesophilic but strictly anaerobic bacteria, metabolizing simple aromatic compounds (Kuever 2014).…”
Section: Anaerobic Microbial Profilementioning
confidence: 99%
“…Nitrosococcus genus are Ammonia Oxidizing Bacteria (AOB), adapted to saline and acidic environments, regularly found in marine environments but less commonly detected in waste water treatment reactors (Fumasoli et al 2017). Mesotoga are frequently found in oil-polluted marine mesophilic anaerobic environments (Nesbø et al 2019). Brooklawnia species are nonmotile, mesophilic, neutrophilic facultative anaerobic bacteria that have been previously identified in chlorosolvent-contaminated environments (da Costa et al 2015) and Syntrophorhabdus are as well nonmotile, mesophilic but strictly anaerobic bacteria, metabolizing simple aromatic compounds (Kuever 2014).…”
Section: Anaerobic Microbial Profilementioning
confidence: 99%
“…The phylum Thermotogota comprises anaerobic fermentative bacteria, most of which are thermophiles (Pollo et al ., 2015). They are common in subsurface environments such as marine vents, terrestrial hot springs and deep subsurface oil reservoirs (Bhandari and Gupta, 2014; Nesbø et al ., 2015, 2019; Foght et al ., 2017). On phylogenetic trees of 16S rRNA gene, Thermotogota is usually a deep branching bacterial lineage, while ribosomal proteins and other markers do not always agree with that placement (Zhaxybayeva et al ., 2009; Hug et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although both prokaryotic cell and virus numbers decrease with depth, the virus-to-cell ratio can increase with depth (Anderson et al, 2013;Engelhardt et al, 2014;Walsh et al, 2016). Phylogeographic studies of hyperthermophilic Thermotoga and mesophilic Mesotoga have revealed genetic interaction between geographically distant populations, particularly among the hyperthermophilic Thermotoga (Nesbø et al, 2015(Nesbø et al, , 2019). Viruses are one potential source of such long-distance dispersal of genetic material (Ochman et al, 2000), especially for anaerobic organisms where surface dispersal is problematic.…”
Section: Introductionmentioning
confidence: 99%
“…The phylum Thermotogota comprises anaerobic fermentative bacteria, most of which are thermophiles [1]. They are found as a deep branching lineage in some universal phylogenetic trees, for example those made from 16S rRNA genes [2], and are common in subsurface environments such as marine vents, terrestrial hot springs and deep subsurface oil reservoirs [3] [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Homologous recombination among closely related genomes is another important evolutionary force acting on Thermotogota genomes [4, 9]. For both the Thermotoga and Mesotoga genera, comparative genomic analyses and analyses of homologous recombination have shown that long fragments of DNA (> 10,000 nucleotides) are transferred between closely related strains [6]. Both types of gene-sharing processes might be driven by viruses.…”
Section: Introductionmentioning
confidence: 99%